Оцінка та регулювання енергоємності ґрунтів України - Тараріко, Ю.О.; Несмашна, О.Ю.; Личук, Г.І. (Український фітоценологічний збірник, 2007)
Рассмотрены методология оценки энергетического состояния почв и возможности регулирования энергоемкости разных типов почв с помощью агротехнических мероприятий. Methodology of estimation of the soil energy state is represented. Possible regulations of energy capacity of soil different types with the help of agrotechnical measures are shown.